RESEARCH ABOUT MUNICIPAL WASTE LANDFILL „SKUĶUPURVS” IMPACT ON ENVIRONMENT - Strods, Andris; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Waste management continues to develop, but it is important to also look back at its past and research environmental impact of old waste landfills. Research showcases determination of municipal waste landfills` “Skuķupurvs” impact on environmental quality. Quality of air, soil and water was determinated.